HIF3A Inhibition Triggers Browning of White Adipocytes via Metabolic Rewiring - Cuomo, Francesca; Dell’Aversana, Carmela; Chioccarelli, Teresa; Porreca, Veronica; Manfrevola, Francesco; Papulino, Chiara; Carafa, Vincenzo; Benedetti, Rosaria; Altucci, Lucia; Cobellis, Gilda; Cobellis, Gilda (Frontiers in Cell and Developmental Biology, 2022)
Maintenance of energy balance between intake and expenditure is a prerequisite of human health, disrupted in severe metabolic diseases, such as obesity and type 2 diabetes (T2D), mainly due to accumulation of white adipose tissue (WAT). WAT undergoes a morphological and energetic remodelling toward brown adipose tissue (BAT) and the BAT activation has anti-obesity potential. The mechanisms or the regulatory factors able to activate BAT thermogenesis have been only partially deciphered. Identifying novel regulators of BAT induction is a question of great importance for fighting obesity and T2D. Here, we evaluated the role of Hif3α in murine pre-adipocyte 3T3-L1 cell line, a versatile and well characterized biological model of adipogenesis, by gain- and loss-of function approaches and in thermogenesis-induced model in vivo. HIF3A is regulated by inflammation, it modulates lypolysis in adipose tissue of obese adults, but its role in energy metabolism has not previously been investigated. We characterized gene and protein expression patterns of adipogenesis and metabolic activity in vitro and mechanistically in vivo. Overexpression of Hif3α in differentiating adipocytes increases white fat cells, whereas silencing of Hif3α promotes “browning” of white cells, activating thermogenesis through upregulation of Ucp1, Elovl3, Prdm16, Dio2 and Ppargc1a genes. Investigating cell metabolism, Seahorse Real-Time Cell Metabolism Analysis showed that silencing of Hif3α resulted in a significant increase of mitochondrial uncoupling with a concomitant increase in acetyl-CoA metabolism and Sirt1 and Sirt3 expression. The causal Hif3α/Ucp1 inverse relation has been validated in Cannabinoid receptor 1 (CB1) knockout, a thermogenesis-induced model in vivo. Our data indicate that Hif3α inhibition triggers “browning” of white adipocytes activating the beneficial thermogenesis rewiring energy metabolism in vitro and in vivo. HIF3A is a novel player that controls the energy metabolism with potential applications in developing therapy to fight metabolic disorders, as obesity, T2D and ultimately cancer.